(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the artistic interpretations of the social environment in which he lived in the stories "Silence" and "The Mask of the Red Death" by the American writer, poet, critic and editor Edgar Allan Poe, the famous founder of the adventure (detective) genre in world fiction. In the stories of the writer, the struggle for human will and spirituality, the ability to present the scenes of the spiritual world in attractive ways, fantastic realism, and the poetics of adventure are highlighted through comparative analysis.